PROFIL TINGKAT KECEMASAN ATLET TERBANG LAYANG PON XX PAPUA TAHUN 2021 - Fladimir Sefanya Mnusefer; Nasruddin, Nasruddin; Junalia Muhammad; Yohanis M. Mandosir (Jurnal Cakrawala Ilmiah, 2023)
When facing the competition situation, the anxiety that must exist before competing is anxiety within normal limits, namely as an athlete's mental readiness to face the match. If the athlete has high anxiety in facing the match, the strategies, tactics and techniques that have been prepared well before the match, will no longer be useful to produce a good performance. This study aims to determine the anxiety level profile of PON XX Papua kite flying athletes in 2021. The research method used in this study is a descriptive method. The variable in this study is a single variable, namely the level of anxiety. The sample in this study amounted to 12 people. The data analysis technique used in this study is to use descriptive analysis techniques with categorization. Results of data analysis, it shows: the anxiety level of PON XX Papua kite flying athletes in 2021 who have low anxiety levels is 10 people (83.3 %), athletes who have moderate anxiety levels are 2 people (16.7%), while athletes who having a high level of anxiety is 0/ none (0%). Thus, almost all Papuan kite flying athletes at PON XX have low anxiety levels